Authigenic εNd offsets driven by sediment–pore water exchange: evidence from the Iberian margin - Sara Campderrós; Leopoldo D. Pena; Jaime Frigola; Luke Skinner; Dimitris Evangelinos; Ester Garcia-Solsona; Eduardo Paredes-Paredes; Albert Català; Isabel Cacho (Geochimica et Cosmochimica Acta, 2026)

Sea Surface Temperature dynamics in the Ligurian Sea during the last 27.4 ka: Disentangling continental, Atlantic and ecological signals of the Globigerina bulloides Mg/Ca-based SST record - Pierluigi Martinelli; Albert Català; Isabel Cacho; Laura Bronzo; Antonio Cascella; Fabrizio Lirer; Mar Selvaggi; Rocco Gennari (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Deglacial and Holocene variability of intermediate water masses in the Ligurian Sea based on a multi-proxy approach - Mar Selvaggi; Isabel Cacho; José N. Pérez-Asensio; Dimitris Evangelinos; Pierluigi Martinelli; Laura Bronzo; Albert Català; Leopoldo D. Pena; Jaime Frigola; Rocco Gennari; Sergio Bonomo; Antonio Cascella; et al. (Quaternary Science Reviews, 2026)

Increase the magnification, they are shrinking! Morphometric variations of the planktic foraminifera Globigerina bulloides in response to environmental changes over the last 27.4 ka in the Ligurian Sea - Pierluigi Martinelli; Isabel Cacho; Elena Cavallero; Antonio Cascella; Letizia Di Bella; Fabrizio Lirer; Mar Selvaggi; Rocco Gennari (Marine Micropaleontology, 2026)

Sediment provenance and transport pathways along the Atlantic Iberian Margin - Sara Campderrós; Leopoldo D. Pena; Ester Garcia-Solsona; Eduardo Paredes-Paredes; Albert Català; Jaime Frigola; Negar Haghipour; Isabel Cacho (Earth and Planetary Science Letters, 2026)

Inflammatory dietary potential and gut microbiota in older adults with overweight or obesity and metabolic syndrome - Héctor Vázquez-Lorente; Adrián Hernández-Cacho; Jesús F. García-Gavilán; Jun Li; Miguel Ruiz-Canela; Clara Belzer; Jesús Vioque; Dolores Corella; Montserrat Fitó; Josep Vidal; Prokopis Konstanti; Isabel Moreno-Indias; et al. (Food Research International, 2025)

Filling the gap of the late Quaternary planktonic foraminifera record in the Western Mediterranean: Paleoceanographic changes in the Ligurian Sea over the last 27.4 ka - Pierluigi Martinelli; Laura Bronzo; Sergio Bonomo; Isabel Cacho; Antonio Cascella; Letizia Di Bella; José-Abel Flores; Jaime Frigola; Fabrizio Lirer; Fabrizio Michelangeli; Mar Selvaggi; Francisco J. Sierro; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Environmental conditions controlling cold-water coral growth in the southern Alboran Sea since the last deglaciation - Mar Selvaggi; Maria de la Fuente; José N. Pérez-Asensio; Claudio Lo Iacono; Albert Català; Sergio Trias-Navarro; Guillem Corbera; Sara Campderrós; Negar Haghipour; Letizia Di Bella; David Van Rooij; Isabel Cacho (Global and Planetary Change, 2025)

Contourite stratigraphic models linked to the light intermediate versus dense deep Mediterranean water flow regime variations (Alboran Sea, SW Mediterranean) - Belén Alonso; Gemma Ercilla; Carmen Juan; Nieves López-González; Isabel Cacho; Guillermo Francés; Desirée Palomino; Patricia Bárcenas; Mariano Yenes; José Nespereira; Blanca Ausín; Pilar Mata; et al. (Marine Geology, 2023)

Solar forcing for nutricline depth variability inferred by coccoliths in the pre-industrial northwestern Mediterranean - Alessandro Incarbona; Sergio Bonomo; Isabel Cacho; Fabrizio Lirer; Giulia Margaritelli; Delia Pecoraro; Patrizia Ziveri (Global and Planetary Change, 2023)

Virus is a Signal for the Host Cell - Jordi Gómez; Ascensión Ariza-Mateos; Isabel Cacho (Biosemiotics, 2015)

Climate controls on rainfall isotopes and their effects on cave drip water and speleothem growth: the case of Molinos cave (Teruel, NE Spain) - Ana Moreno; Carlos Sancho; Miguel Bartolomé; Belén Oliva-Urcia; Antonio Delgado-Huertas; Mª José Estrela; David Corell; Juan Ignacio López-Moreno; Isabel Cacho (Climate Dynamics, 2014)

Influences of extratropical water masses on equatorial Pacific cold tongue variability during the past 160 ka as revealed by faunal evidence of planktic foraminifers - Pai‐Sen Yu; Markus Kienast; Min‐Te Chen; Isabel Cacho; Jos Abel Flores; Mahyar Mohtadi; Alan C. Mix (Journal of Quaternary Science, 2012)
Glacial cooling (∼1–5°C) in the eastern equatorial Pacific (EEP) cold tongue is often attributed to increased equatorial upwelling, stronger advection from the Peru–Chile Current (PCC), and to the more remote subpolar southeastern Pacific water mass. However, evidence is scarce for identifying unambiguously which process plays a more important role in driving the large glacial cooling in the EEP. To address this question, here we adopt a faunal calibration approach using planktic foraminifers with a new compilation of coretop data from the eastern Pacific, and present new downcore variation data of fauna assemblage and estimated sea surface temperatures (SSTs) for the past 160 ka (Marine Isotope Stage (MIS) 6) from ODP Site 1240 in the EEP. With significant improvement achieved by adding more coretop data from the eastern boundary current, our downcore calibration results indicate that most of the glacial cooling episodes over the past 160 ka in the EEP are attributable to increased influence from the subpolar water mass from high latitudes of the southern Pacific. By applying this new calibration of the fauna SST transfer function to a latitudinal transect of eastern Pacific (EP) cores, we find that the subpolar water mass has been a major dynamic contributor to EEP cold tongue cooling since MIS 6. Copyright © 2012 John Wiley & Sons, Ltd.